Ectopic Expression in Arabidopsis thaliana of an NB-ARC Encoding Putative Disease Resistance Gene from Wild Chinese Vitis pseudoreticulata Enhances Resistance to Phytopathogenic Fungi and Bacteria - Wen, Zhifeng; Yao, Liping; Wan, Ran; Li, Zhi; Liu, Chonghuai; Wang, Xiping (Frontiers in Plant Science, 2015)
Plant resistance proteins mediate pathogen recognition and activate innate immune responses to restrict pathogen proliferation. One common feature of these proteins is an NB-ARC domain. In this study, we characterized a gene encoding a protein with an NB-ARC domain from wild Chinese grapevine Vitis pseudoreticulata accession “Baihe-35-1”, which was identified in a transcriptome analysis of the leaves following inoculation with Erysiphe necator (Schw.), a causal agent of powdery mildew. Transcript levels of this gene, designated VpCN (GenBank accession number KT265084), increased strongly after challenge of grapevine leaves with E. necator. The deduced amino acid sequence was predicted to contain an NB-ARC domain in the C-terminus and an RxCC-like domain similar to CC domain of Rx protein in the N-terminus. Ectopic expression of VpCN in Arabidopsis thaliana resulted in either a wild-type phenotype or a dwarf phenotype. The phenotypically normal transgenic A. thaliana showed enhance resistance to A. thaliana powdery mildew Golovinomyces cichoracearum, as well as to a virulent bacterial pathogen Pseudomonas syringae pv. tomato DC3000. Moreover, promoter::GUS (β-glucuronidase) analysis revealed that powdery mildew infection induced the promoter activity of VpCN in grapevine leaves. Finally, a promoter deletion analysis showed that TC rich repeat elements likely play an important role in the response to E. necator infection. Taken together, our results suggest that VpCN contribute to powdery mildew disease resistant in grapevine.